Regulation of endometrial cancer cell growth by luteinizing hormone (LH) and follicle stimulating hormone (FSH) - Davies, S (Nature Publishing Group, 2000)
Gonadotrophin releasing hormone analogues (GnRHa) have been used to treat recurrent endometrial cancer. However, the mode of action is uncertain. Our previous studies showed no direct effect of GnRHa on endometrial cancer cell growth in vitro. We have now examined the effect of luteinizing hormone (LH) and follicle stimulating hormone (FSH) on endometrial cancer cell growth. The aim was to determine whether suppression of pituitary LH and FSH by GnRHa could explain the tumour regression seen in up to 44% of patients treated with this drug. We show that recombinant human LH and FSH (rhLH and rhFSH) produce a concentration dependent stimulation of the endometrial cancer cell line HEC-1A, in serum-free medium (maximum increase of 62 and 50% respectively relative to untreated controls). This increase is equivalent to that obtained by addition of 10% newborn calf serum. Growth of the Ishikawa cell line in culture increases in the presence of rhLH (maximum increase of 67%) but not with rhFSH. Using RT-PCR, we show that the Ishikawa cell line intermittently expresses receptor mRNA of LH but not of FSH; there is no expression of either mRNA by HEC-1A. Classically, both LH and FSH act via cAMP linked membrane receptors. However, neither rhLH nor rhFSH elicit cAMP production in either of our endometrial cancer cell lines. Thus, although a growth response to LH and FSH can be shown, and some cells express the LH receptor, stimulation appears to be via a pathway separate from that of the classical gonadotrophin receptor. © 2000 Cancer Research Campaign http://www.bjcancer.com